Effect of Fabrication Technique on the Marginal Discrepancy and Resistance of Lithium Disilicate Crowns: An In Vitro Study. Issue 9 (22nd January 2019) - Sadid‐Zadeh, Ramtin; Li, Rui; Miller, Lorin M.; Simon, Michael
Abstract: Purpose: To evaluate the impact of fabrication technique on the marginal fit and resistance of lithium disilicate crowns. Materials and Methods: Twelve ivorine molars were prepared to receive lithium disilicate crowns. The preparations were digitally recorded using an intraoral scanner, and the crowns were designed following the anatomy of an unprepared tooth using a design software. The designed crowns were fabricated using 3 techniques: (1) milling from lithium disilicate blocks using a 3‐axis milling machine (3XM), (2) milling from lithium disilicate blocks using a 5‐axis milling machine (5XM), and (3) milling from resin‐wax billet using a 5‐axis milling machine, followed by heat‐pressing the pattern into lithium disilicate (5XWP). For the control group, the wax patterns were fabricated by one lab technician, and the crowns were fabricated by heat‐pressing the pattern into lithium disilicate (CWP). After sintering, the crowns were secured on their associated preparations using an elastomeric material. The marginal gap of each crown was then measured at 14 defined locations through analyses of 20× images captured with a stereomicroscope. The marginal integrity and resistance to rotation of each crown were assessed by 2 calibrated practitioners. Differences in outcomes by fabrication technique were assessed using Wilcoxon, Kruskal Wallis, and Fisher's exact tests, as appropriate (α = 0.05). Results: Crowns fabricated using digital workflows (3XM, 5XM, 5XWP) had significantly smaller mean marginal gaps compared to the CWP group ( p = 0.0001, p = 0.0002, p = 0.0001, respectively); however, 3XM group was the only group to exhibit significantly better marginal integrity than the CWP group ( p = 0.0004). No significant difference ( p = 0.6004) in the resistance to rotation of crowns was observed between groups. Conclusions: Choice of fabrication technique and instrument may impact the marginal discrepancy of lithium disilicate crowns; however, all fabrication techniques analyzed produced crowns with acceptable marginal discrepancies.